Multivalued generalizations of fixed point results in fuzzy metric spaces - Tatjana Došenovic; Dušan Rakic; Biljana Caric; Stojan Radenovic (Nonlinear Analysis, 2016)
This paper attempts to prove fixed and coincidence point results in fuzzy metric space using multivalued mappings. Altering distance function and multivalued strong {bn}-fuzzy contraction are used in order to do that. Presented theorems are generalization of some well known single valued results. Two examples are given to support the theoretical results.